(untitled) (Journal of Forensic Medicine & Toxicology, 2020)
In overview stage G, maxillary right and left third molar with mandibular right third molars are considerable variability in age prediction. It was concluded that the eight stage system was less prone to examiner error. Finally, we believe that, based on our results, and the differences between them and those of other populations, where in agreement with mincer et al. present study shows better accuracy. Nevertheless, this remains as an yet to be proven concept since there is no indication at all regarding the use of country-specific information influencing the percentage of correctly identified subject.